Text, context and performance: Gagauz folk religion in discourse and practice - Kapaló, James (Studies in the history of religions, 2011)
Chapter Four Language, Lay Agency and the 'Surrogate' Text Bu epistolii yazdı kendi Allah -- 'This letter was written by God himself 'Russian, Moldovan and Gagauz Apocalypticism; Epistoliyas and Apocalyptic Texts in the Gagauz Language; Translations, Translators and Tetratkas; Epistoliyas in Folk Religious Practice; Conclusion; Chapter Five Healing and Divine Authority Düştän Allahın lafı sana geldi! -- 'The words of God have come to you in a dream'; The Traditional Healing System; The İlaççılar; Conclusion.